Affective governance as multimodal discursive practice in Singapore' COVID-19 vaccination video. Issue 2 (June 2022) - Xu, Huimin; Weninger, Csilla
Drawing on scholarship on affective-discursive practice and employing a critical multimodal analytic approach, this paper examines how an official vaccination campaign video from Singapore affectively engages with audiences through the construction of various social relationships and identities. Analysis of the multimodal images identifies four salient themes in the video: (1) a harmonious neighborhood comprising inter-ethnic friendships, (2) a paternalistic father-child relationship, (3) a male-dominant family model, and (4) a nostalgic past-present relationship. The analysis shows that affect is discursively mobilized in the orchestration of embodied modes, auditory, and visual modes via strategic filming and editing techniques. Based on the analysis, the authors argue that the video not only functions to subtly persuade the public to get vaccinated but should also be seen as part of a broader move toward an 'affective politics' which aims to mobilize the public, reinforce social cohesion and manage the global pandemic crisis in contemporary Singapore.